MODIFICAR EL PROCEDIMIENTO PARA EL COBRO DE PENSIONES ALIMENTICIAS PARA LAS VICTIMAS DE VIOLENCIA INTRAFAMILIAR ESTABLECIDAS EN EL CÓDIGO ORGÁNICO INTEGRAL PENAL - ORTIZ CALVA, CRISTIAN JAVIER (2016)
Domestic violence is not a distant issue of our society unfortunately is as old as man, in our society, one could say that almost all Ecuadorian households have felt about this problem, same as we have been dragging on from generation to generation, but with the new legal system is intended to reduce these violations, interest is socio-legal, it is clear that the laws intended that this social problem affecting the core of it is the family, is decreased, and achieve a better family, a better society. The issue of domestic violence legislation has been gaining ever greater connotation, so much so that now with Integral Organic Penal Code, which came into force in 2014, have been implemented more protective measures for the victim and more penalties for the perpetrator. However, leaving it clear that the violated rights are those of the victim and are ones that require immediate legal action, you can not ignore the aggressor, but has committed an offense, you have rights which must be respected, and the implementing aggressive measures even undermine the constitutional law already established, nor against the logic of the law, is not a viable solution to the problem of domestic violence. In Art. 643, section 7, paragraph 2, of the Code of Criminal Integral, states that whoever does not comply with the protective measures granted to the victim, nor alimony in favor of the victim should be necessary, It will consider it as a subject who disobeys a lawful order of an authority, which would lead to an investigation by the Prosecutor, as goes without mentioning that it is an 5 aggressive measure, which leaves out important methods to get it done effective the obligation, such as are the actual measurements. With these aggressive measures, not only that damage would be caused to the aggressor, but the entire prison system, as it could seriously cause overcrowding, besides taking care of the detainees generates strong economic costs to the country. The solution is not to implement stronger measures but viable measures that can be made really effective, that is not only to punish the perpetrators of domestic violence, but also as far as possible repair the damage caused to the victim.